T‐ and L‐Type Voltage‐Gated Calcium Channels: Their Role in Diabetic Bladder Dysfunction. Issue 1 (12th March 2013) - Jiang, Xiaogang; Luttrell, Ian; Chitaley, Kanchan; Yang, Claire C.
Abstract Aims We investigated the mechanisms of diabetic bladder dysfunction (BD) through analysis of the roles of L‐ and T‐type voltage‐gated calcium channels (VGCCs), with the ultimate goal of identifying potential drug targets for diabetic BD. Methods Bladder function of db/db (type 2 diabetes) and wild type (Wt) mice was evaluated by behavioral tests and in vivo cystometry. Contractile responses of bladder strips to carbachol were measured with or without pre‐treatment with nifedipine (a L‐type VGCC blocker) or mibefradil (a T‐type VGCC blocker). Furthermore, the effects of mibefradil and nifedipine on the proliferation of human bladder smooth muscle cells (BSMCs) were studied. Results db/db mice had significantly increased voiding frequency, bladder weight, bladder compliance and capacity, and heightened contractile response to carbachol, compared to Wt mice. Nifedipine, but not mibefradil, dramatically suppressed bladder tissue contraction in Wt mice. Whereas nifedipine nearly completely inhibited bladder contraction in db/db mice, mibefradil "normalized" the heightened bladder contractility of db/db mice to the level of Wt mice. In culture, mibefradil, but not nifedipine, inhibited the proliferation of human BSMCs. Conclusion Our results indicate that while L‐type VGCCs play a major role in the contraction of both diabetic and non‐diabetic bladders, T‐type VGCCs are involved in the contraction of diabetic bladders and mediate BSMC proliferation. This study provides support for further investigations on the effect of blockade of T‐type VGCC or combined blockade of both types of VGCCs in the treatment of diabetic BD. Neurourol. Urodynam. 33:147–152, 2014. © 2013 Wiley Periodicals, Inc.